Precipitation processes and structural evolutions of various GPB zones and two types of S phases in a cold-rolled Al-Mg-Cu alloy. (1st February 2021) - Chen, Xuanliang; Marioara, Calin D.; Andersen, Sigmund J.; Friis, Jesper; Lervik, Adrian; Holmestad, Randi; Kobayashi, Equo
Abstract: The Guinier–Preston–Bagaryatsky (GPB) zone and the S phase are the key strengthening precipitates in Al-Cu-Mg alloys. However, how their respective structures evolve during aging has not been fully understood. In this work, the age-hardening behavior and the precipitates in an Al–3Mg–1Cu (wt.%) alloy were investigated by means of Vickers hardness measurements, differential scanning calorimetry, transmission electron microscopy, and density functional theory calculations. A series of common GPB zones and a novel type of GPB zone named "GPBX" were observed in the cold-worked samples aged at 443 K for 20 min. In the subsequent aging, two types of S phases were found to coexist, labeled S-I and S-II phases. Density functional theory calculation results indicate that GPBX zone is stable and the S-I and S-II phases have almost the same formation enthalpy. Common GPB zones transform to S-I phases, while S-II phases are formed from GPBX zones preferentially along dislocation lines. The misorientation angles and morphologies of the S phases are also discussed. GPB zones were confirmed to be structurally linked to β" and U2 precipitates reported in 6xxx (Al-Mg-Si) series Al alloys. The revealed precipitate structures and their interrelationships may provide insights into future alloy design. Graphical abstract: Unlabelled Image Highlights: A novel type of GPB zone named "GPBX" is observed. The crystal structure of S-II phases is determined as monoclinic. The precipitation process, structural evolution and growth mechanisms of GPB zones and S phases are proposed. The complex structure mixed of different types of precipitates is confirmed.